2009
DOI: 10.4081/rt.2009.e10
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary Capillary Hemangioma of the Thoracic Spine: Case Report and Review of the Literature

Abstract: Capillary hemangiomas are benign vascular neoplasms. When associated with the spine, these growths frequently involve the vertebral body, but rarely have they been reported to occur as intradural lesions, while even more rarely occurring in a true intramedullary location. We report a rare case of an intramedullary capillary hemangioma of the thoracic spinal cord and a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…Although there are no previous reports on venous angiomas inside the cord, such as in our patient, reports on cavernous angiomas showed that approximately 50% of the patients presented with progressive deficits while the remaining presented with acute or recurrent symptomatology [11]. Progressive neurological deterioration can be confused with demyelinating pathologies, myelitis, intramedullary tumors and spinal arteriovenous malformations [11,12]. The co-existed neurofibromatosis (NF-1) with the big café-au-lait spots and the advanced scoliosis that increased from initially 24° to 44° made early diagnosis not possible although one should expect that such an increase should raise natural suspicions!…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Although there are no previous reports on venous angiomas inside the cord, such as in our patient, reports on cavernous angiomas showed that approximately 50% of the patients presented with progressive deficits while the remaining presented with acute or recurrent symptomatology [11]. Progressive neurological deterioration can be confused with demyelinating pathologies, myelitis, intramedullary tumors and spinal arteriovenous malformations [11,12]. The co-existed neurofibromatosis (NF-1) with the big café-au-lait spots and the advanced scoliosis that increased from initially 24° to 44° made early diagnosis not possible although one should expect that such an increase should raise natural suspicions!…”
Section: Discussionmentioning
confidence: 52%
“…The existence of cryptic veins together with small cavernous angiomas has been reported in the literature [10]. Although there are no previous reports on venous angiomas inside the cord, such as in our patient, reports on cavernous angiomas showed that approximately 50% of the patients presented with progressive deficits while the remaining presented with acute or recurrent symptomatology [11]. Progressive neurological deterioration can be confused with demyelinating pathologies, myelitis, intramedullary tumors and spinal arteriovenous malformations [11,12].…”
Section: Discussionmentioning
confidence: 58%
“…advised to avoid massive bleeding intraoperatively, which has been advocated in the previously published series. 3,7,8 In our cases laminectomy was performed, and the lesion surface was easily found intraoperatively. Most of the lesions showed no adhesion to the spinal cord, and complete removal was achieved easily using microsurgical techniques.…”
Section: Discussionmentioning
confidence: 99%
“…CH as intradural extramedullary (IDEM) tumor in spine is extremely rare and difficult to differentiate with other common pathologies10,21). Despite of the low incidence, prompt diagnosis and complete resection area important, because acute hemorrhage leading to sudden neurologic deterioration can be occurred17).…”
Section: Introductionmentioning
confidence: 99%